"MUSIC AND SOCIETY": ”संगीत एवं समाज” - Mishra, Geeta (International Journal of Research -GRANTHAALAYAH, 2015)
"Music" is a unique creation of the universe, which transmits the senses of the conscious mind of the human being in the pastoral world to create a feeling of unlimited bliss. Innovation in music is the transmission of the emotion of the mind, which is influenced by the environment. Along with the creation and development of the universe, the expression of intensely sensitive feelings of the human mind was communicated in the form of nad (music). Brahm Swaroop "Nad" has contributed significantly in setting the human mind to the pinnacle of divinity by enlightening the Veda knowledge. ‘‘संगीत‘‘ सृष्टि की अनुपम कृति है,जो चराचर जगत में मानव केे चेतन मन की संवेदनाओं को संचारित करके असीम आनंद की अनुभूति कराती है। संगीत में नवाचार मन के संवेग का संचरण है,जो वातावरण से प्रभावित होता है। सृष्टि की रचना एवं विकास के साथ साथ ही मानव मन की तीव्र संवेदनशील भावनाओं की अभिव्यक्ति का संचार नाद(संगीत) के रूप में हुआ। ब्रह्म स्वरूप ”नाद” ने वेद ज्ञान को सामगान से आलोकित करके मानव मन को देवत्व के शिखर पर स्थापित करने में महत्वपूर्ण योगदान दिया है।